Strength and conditioning for combat sports athletes - Emerson Franchini; Tomás Herrera-Valenzuela (Revista de Artes Marciales Asiáticas, 2021)
Editors • Emerson Franchini – University of São Paulo, São Paulo (Brazil) • Tomás Herrera-Valenzuela – Universidad de Santiago de Chile (Chile)